The Determinants of Pediculosis capitis Incidence in Female Students of the Integrated Islamic School of Raudhatul Ulum - Sari, Intan Permata; Sunarsih, Elvi; Septiyani, Kartika Putri (Sarana Ilmu Indonesia (Salnesia), 2025)
Pediculosis capitis is an infestation of the human skin and scalp by the parasitic pest Pediculus humanus capitisIts prevalence was reported to be high and variable worldwide. The estimated prevalence of Pediculosis capitis in Indonesia is 29%. Pediculosis capitis in children can cause decreased health and cognitive performance. This study aimed to determine the prevalence and determinants of Pediculosis capitis among female students at the Raudhatul Ulum Integrated Islamic School. The study was conducted cross-sectionally with 132 subjects using a multistage sampling technique. The independent variables in the study were humidity, occupancy density, use of shared combs, use of shared headscarves, use of shared mukena and use of shared pillows with the dependent variable Pediculosis capitis. Bivariable statistical analysis concluded that there was no significant correlation between room humidity (p-value 0,087) and occupancy density factors (p-value = 0,776). There was a significant correlation between the variables of use of shared mukena (p-value <0,001), use of shared pillows (p-value <0,001), use of shared combs (p-value <0,001), and use of shared headscarves (p-value <0,001) with the incidence of Pediculosis capitis in female students at the Raudhatul Ulum Sakatiga Islamic Boarding School. The use of mukena was the dominant variable influencing Pediculosis capitis in female students controlled by other variables (PR = 20,812). There were four related variables and two unrelated variables in the results of the research analysis. It is hoped that every Islamic boarding school institution will pay attention to the cleanliness and health of its students.